Isolation and characterization of viruses infecting Acidobacteria from Arctic soil - Marttila, Heli (Helsingin yliopisto, 2021)
Global warming affects permafrost in the Arctic regions, where melting organic carbon storages will increasingly contribute to the emission of greenhouse gases. Little is known about tundra soil microbial communities, but Acidobacteria and viruses seem to have important roles there. Here, for the first time, we isolated five Acidobacteria infecting viruses from Kilpisjärvi tundra soils using host strains previously isolated from the same area. Three viruses were isolated on Edaphobacter sp. X5P2, one on Edaphobacter sp. M8UP27, and one on Granulicella sp. X4BP1. The viruses had circular double-stranded DNA genomes 63,196–308,711 bp in length and 51–58% GC content. From 108 to 348 putative ORFs were predicted, 54–72% of which were sequences unique to each virus. Annotations indicated that all five phages most likely have tailed virions. The diversity of viruses present in the studied soils was estimated with the metagenome analysis. Only 0.1% (627) of all assembled metagenomic contigs were phage-positive. The gene-sharing network analysis showed approximately genus-level clustering between the virus isolates and a few metagenomic viral contigs, but overall, all (except one) viral contigs clustered only with each other, not with any known viruses from the NCBI database. No taxonomical assignments could be done for the metagenomic viral contigs, highlighting overall undersampling of soil viruses. Further detailed studies on virus-host interactions are needed to understand the impact of viruses on host abundance and metabolism in Arctic soils, as well as the microbial input into biogeochemical cycles.